Pembelajaran Bernyanyi Secara Daring Di Kelas VIII A SMP Negeri 8 Kota Padang - Muhammad Abdika; Harisnal Hadi (FBS Universitas Negeri Padang, 2021)
This study aims to identify and describe the online learning implementation of Cultures dan Arts at SMP Negeri 8 Padang. This research used descriptive qualitative method. The main instrument in this study was the researcher itself as the main instrument and was assisted by supporting instruments such as writing tools and cellphones. The data were collected through observation, interview, literature study, and document study. Types of data used were primary and secondary data. The data were processed by collecting the data, classifying the data, analyzing the data, describing the data, and drawing the conclusion. The results show that the online learning implementation of Cultures and Arts subject of music material in class VIII. A at SMP Negeri 8 Padang is constrained by distance so that the quality of learning result is not optimal. The lesson plan made still refers to the old one, namely RPP Semester Juli - December 2019. The online learning of Cultures and Arts, at SMP Negeri 8 Padang, under the topic of styles and techniques in singing traditional songs does not work effectively. In this online learning, several problems were found. For instance, the teacher was unable to directly monitor students who actually attended the lesson, and some students did not understand the material provided by the teacher. As a conclusion, an adjustment from both the teacher and students is needed so that the learning objectives can be achieved as expected.